GREEN TOURIST ANALYSIS IN KOTA TUA JAKARTA - Rohma, Septi Nurlela; Ertikasari, Callista Cindy; Wibowo, Abraham Septian; Agustin, Rizki Suzan; Safitri, Nurlaili; Maulina, Anita (Universitas Nusa Cendana, 2025)
This study seeks to identify and examine the variables of attitude, subjective norms, and behavioral controls that influence green tourist behavior. Green tourists are those who consider eco-friendliness when visiting tourist attractions. The methodology utilized in this study is quantitative. The application Smart-PLS assisted with statistical data analysis using structural equation modeling (SEM-PLS). Respondents used up to 177 tourists who visited Kota Tua Jakarta within a specific period. The study's findings revealed that attitude, subjective norms, and behavioral controls all have a positive and significant influence on green tourist behavior. This study has some limitations, including a small number of respondents, a short questionnaire collection period, and the use of just a quantitative approach. Recommendations for additional research are made so that the green tourist theme can become knowledge to support sustainable tourism. Keywords : Attitude; Subjective Norm; Behavioral Control; Green Tourist Behavior; Kota Tua Jakarta